0857 The Influence of Obesity on the Association of Sleep Apnea and Atrial Fibrillation. (12th April 2019) - Stafford, Patrick; Harrison, Elizabeth; Patel, Paras; Walker, McCall; Cho, Yeilim; Mazimba, Sula; Bilchick, Kenneth; Kwon, Younghoon
Abstract: Introduction: The association of obstructive sleep apnea (OSA) with atrial fibrillation (AF) has been well-described. However, obesity is a powerful confounder in the causal relationship between OSA and cardiovascular disease. The role of obesity in the relationship of OSA and AF remains unclear. Methods: We identified an equal number of consecutive patients with and without AF who underwent clinically indicated diagnostic polysomnography at a single academic sleep center. OSA was defined by AHI >15/hr, with severe OSA being AHI >30/hr. Obesity was defined as BMI >30kg/m 2 . Multivariable logistic regression adjusting for age, sex, hypertension, and heart failure (HF) was performed to examine the independent association between OSA and AF stratified by obesity. Results: A total of 457 patients (male: 56%, mean age 62.6± 14.0 years) were included. There was a high prevalence of HF in the AF cohort (67.7%; low vs. high BMI group; 56.3% vs. 80%, p=0.0001). OSA prevalence was similar between those with and without AF (57.2% vs. 51.8%, p=0.24). The prevalence of OSA was higher in patients with AF in the non-obese group (47.1% vs. 60.5%, p= 0.037), but not in obese patients (57.0% vs. 53.6%, p=0.62). However, this association in non-obese group was lost in multivariable logistic analysis (OR 1.11 [0.59-2.08], p=0.74). Sensitivity analysis showed that presence of AF was associated with severe OSA in the non-obese group (OR 2.19 [1.08-4.48], p=0.03). Analysis excluding patients with HF yielded similar results. Among patients without AF or HF, age (OR 2.01, [1.02-4.06]), obesity (OR 1.86, [1.01-3.48]), and gender (OR 2.09, [1.16-3.80]) were risk factors associated with OSA. In those with both AF and HF, only male sex (OR 3.03, [1.51-6.19]) was associated with OSA. Conclusion: In high risk AF patients, the association of AF with OSA was present only in the non-obese, and was limited to severe OSA patients. In contrast no association was found in obese patients. This suggests that the association between AF and OSA is partly dependent on the body habitus. Support (If Any): None